1999
DOI: 10.1038/sj.bjc.6690727
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of N-acetyltransferase 1 and 2 and risk of cigarette smoking-related bladder cancer

Abstract: Aromatic amines from cigarette smoking or occupational exposure, recognized risk factors for bladder cancer, are metabolized by N -acetyltransferases (NAT). This study examined the association of (NAT) 1 and 2 genotypes with the risk of smoking-related bladder cancer. A total of 74 pathologically confirmed bladder cancer patients and 184 controls were serially recruited from the National Taiwan University Hospital. History of cigarette smoking and other risk factors for bladder cancer wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 20 publications
1
35
0
Order By: Relevance
“…A previous review of 21 published case-control studies reported that experimental evidence was not sufficient to conclude a real increase in risk for urinary bladder cancer in slow NAT2 acetylators (Green et al, 2000). However, subsequent studies carried out in Europe (Vineis et al, 2001), Japan (Tsukino et al, 2004), the United States (Gu et al, 2005) and Spain (Garcia-Closas et al, 2005) each reported that NAT2 slow acetylators had a significantly increased risk of urinary bladder cancer that was stronger in smokers, (Woodhouse et al, 1982;Miller and Cosgriff, 1983;Hanssen et al, 1985;Ladero et al, 1985;Mommsen and Wolf, 1985;Karakaya et al, 1986;Kaisary et al, 1987;Horai et al, 1989;Dewan et al, 1995;Ishizu et al, 1995;Risch et al, 1995;Peluso et al, 1998;Su et al, 1998;Taylor et al, 1998;Hsieh et (Tsukino et al, 2004). Meta-analysis of these and all previous studies show that the overall association with slow NAT2 genotype in the published literature is robust (Figure 7) providing compelling evidence for a role of NAT2 acetylator genotype in urinary bladder cancer associated with aromatic amines in cigarette smoke.…”
Section: Nat2 Polymorphism and Urinary Bladder Cancer Riskmentioning
confidence: 99%
“…A previous review of 21 published case-control studies reported that experimental evidence was not sufficient to conclude a real increase in risk for urinary bladder cancer in slow NAT2 acetylators (Green et al, 2000). However, subsequent studies carried out in Europe (Vineis et al, 2001), Japan (Tsukino et al, 2004), the United States (Gu et al, 2005) and Spain (Garcia-Closas et al, 2005) each reported that NAT2 slow acetylators had a significantly increased risk of urinary bladder cancer that was stronger in smokers, (Woodhouse et al, 1982;Miller and Cosgriff, 1983;Hanssen et al, 1985;Ladero et al, 1985;Mommsen and Wolf, 1985;Karakaya et al, 1986;Kaisary et al, 1987;Horai et al, 1989;Dewan et al, 1995;Ishizu et al, 1995;Risch et al, 1995;Peluso et al, 1998;Su et al, 1998;Taylor et al, 1998;Hsieh et (Tsukino et al, 2004). Meta-analysis of these and all previous studies show that the overall association with slow NAT2 genotype in the published literature is robust (Figure 7) providing compelling evidence for a role of NAT2 acetylator genotype in urinary bladder cancer associated with aromatic amines in cigarette smoke.…”
Section: Nat2 Polymorphism and Urinary Bladder Cancer Riskmentioning
confidence: 99%
“…Since then a large number of studies have appeared in the literature confirming or refuting an association between NAT2 status and bladder cancer risk [Woodhouse et al, 1982;Evans et al, 1983;Miller and Cosgriff, 1983;Hanssen et al, 1985;Ladero et al, 1985;Mommsen et al, 1985;Karakaya et al, 1986;Kaisary et al, 1987;Horai et al, 1989;Hanke and Krajewska, 1990;Hayes et al, 1993;Risch et al, 1995;Brockmoller et al, 1996;Okkels et al, 1997;Schnakenberg et al, 1998;Taylor et al, 1998;Filiadis et al, 1999;Hsieh et al, 1999]. In an attempt to clarify the effect of NAT2 status on bladder cancer risk, a meta-analysis of published studies has been undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…17 Regarding HCC, some studies have observed a significant association with NAT2 genetic polymorphisms, for both slow 18,19 and rapid 20 acetylator genotypes.…”
mentioning
confidence: 99%